Hydrophobic interactions of group A streptococci with hexadecane droplets - Itzhak Ofek; E Whitnack; E H Beachey (1983)
The adherence of Streptococcus pyogenes cells to hexadecane droplets was measured by vortexing water suspensions of streptococci with hexadecane. It was found that adherence of the organisms to hexadecane droplets was abolished by pretreating the organisms with trypsin, pepsin at pH 4.5, or HCl solutions at 95 degrees C. Streptococcal adherence was best expressed in organisms harvested during the stationary phase of growth and was inhibited by fatty acid-free albumin because of the interaction of the protein with the streptococcal surfaces. The data suggest that adherence to hexadecane droplets measures the availability on the surface of S. pyogenes cells of lipophilic residues that are either hydrophobic regions of surface protein structures or, more likely, glycolipids complexed with and oriented by surface proteins.